Strahlen im Kalten Krieg : Nuklearer Alltag und atomarer Notfall in der Schweiz - Marti, Sibylle 1980- (Krieg in der Geschichte, 2021)
“Radiation in the Cold War” investigates the way that politics, science, and society dealt with radiation in Switzerland. The study examines how Switzerland prepared for a future atomic war as well as for nuclear uses in everday life. The history of radiation and radiation protection sheds light on the political culture of Cold War Switzerland that so far has only received little attention